Education and learning in the early Islamic world - Gilliot, Claude (The formation of the classical Islamic world, 2012)
"The studies in this volume have been selected for the critical approaches and methods of their authors, and are arranged under five headings: the pedagogical tradition; scholarship and attestation; orality and literacy; authorship and transmission; and libraries. Together with the editor’s introductory essay, they present a broad picture of the beginnings and evolution of education and learning in the Islamic world" --